Balneoterapi Kontraendikasyonları ve Endikasyonları - Karakaş, Merve (Geçmişten Günümüze Rehabilitasyonda Balneoterapi ve Hidroterapi, 2024)
Balneoterapi tedavisinin etkili olduğu hastalıklar mevcuttur ve bir de her tedavide olduğu gibi uygulanması sonrası hastalığı kötüleştirebileceği durumlarda uygulanması kontraendikedir. Böyle hastalıklarda uygulanması kesinlikle uygun değilken; bazı hastalıklarda dikkatle uygulanabilmektedir. Bu bölümde de bu durumlar detaylıca incelenmiştir. Balneotherapy treatment is effective for certain diseases, and just like in any treatment, there are conditions where its application may worsen the illness, making it contraindicated. While it's definitely not suitable for application in such diseases, in some cases, it can be applied with caution. This section thoroughly examines these situations.